Contextual Conditions for Functioning of Lexemes of Comparative Semantics - R. Li (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
The article is devoted to the analysis of the compatibility of lexemes of comparative semantics sopostavleniye ‘comparison’ and v sopostavlenii s ‘in comparison with’. The question about ways of representation of components of comparative meaning in superficial syntactic structure is considered. The relevance of the study is due to the modern approach to grammar through the prism of semantics. The paper shows the possible ways to verbalize objects of comparison within the construction in a simple sentence. The main attention is paid to the description of typical contexts of the studied lexemes. The novelty of the research lies in the results obtained. The study found out that these tokens are characterized by two types of context: mental and evaluative, which reflects the procedure of comparison as a mental act. Attention is drawn to the fact that the matching parameter is verbalized in the evaluative context type. The semantic classification of mental predicates forming typical contexts of lexemes of comparative semantics is proposed. A comparative analysis is made of typical contexts of the lexeme sopostavleniye and noun relative v sopostavlenii s . The difference is shown both in the types of mental predicates that are specific to each of the tokens and in the types of contexts. It is established that another type of context is typical for the noun relative - existential context. As a result, it is concluded that the difference in typical contexts confirms the fact of started separation of the word form v sopostavlenii s from the paradigm of noun sopostavleniye .